The current state of the transport system of the Republic of Kazakhstan and the problems of its development (Journal of Geography and Environmental Management, 2019)
In the article discusses the current state of the transport system of the Republic of Kazakhstan and theproblems of its development. The results of the study showed that the transport system of the republicin its current state cannot fully meet the needs of the economy, given the huge territory of Kazakhstanand the state programs and plans for the long-term development of the economic potential of the republic.The vast territory of the country, low population density, disunity of the centers of industry andagriculture, as well as remoteness from world markets, makes the possession of a developed transportsystem vital for Kazakhstan. The objectives of the upcoming stage of development of the transport industryin Kazakhstan include increasing the efficiency of activities, new construction of transport infrastructurefacilities, upgrading the existing infrastructure, accelerating product flow and reducing transportcosts, improving safety and sustainability of the industry, as well as the availability of transport services for thepopulation. Kazakhstan is developing international cooperation in the field of transport, that allows the receivenew equipment and technologies, to the country introduces international experience. Considering thecurrent state and problems of the transport system of the republic, the author offers recommendations on thedevelopment of the transport system, which is important in the development of the republic’s economy.